Authority Of Nurses In Installing Infusations Outside Health Care Facilities During The Covid-19 Pandemi - Prihatin Effendi; Moh Nasichin (Fakultas Hukum Dehasen, 2024)
Infusion outside health care facilities is one of the medical actions that nurses can take in certain limited circumstances during the COVID-19 pandemic emergency. The research method used by the author in this research is normative legal research, using three approaches, namely Legislation (Statute Approach), Conceptual Approach, and Comparative Approach. The results of this study explain the authority of nurses and the responsibility of nurses for infusion outside health care facilities during a pandemic, that a nurse in certain limited circumstances during the COVID-19 pandemic emergency has the authority to provide first aid in the form of medical action, namely infusion in accordance with their competence based on statutory provisions in accordance with the nurse's knowledge of assessing the patient's condition. Meanwhile, the responsibility for installing infusions by nurses is personal because it is independent, meaning that if an error occurs in the action, the nurse concerned will bear his own responsibility.